Evidence for under-diagnosis of childhood acute lymphoblastic leukaemia in poorer communities within Great Britain. - Kroll, M; Stiller, C; Richards, S; Mitchell, C; Carpenter, L (2012)
BACKGROUND: Recorded incidence of childhood acute lymphoblastic leukaemia tends to be lower in poorer communities. A 'preemptive infection hypothesis' proposes that some children with leukaemia die from infection without diagnosis of leukaemia. Various different blood abnormalities can occur in untreated leukaemia. METHODS: Logistic regression was used to compare pre-treatment blood counts among children aged 1-13 years at recruitment to national clinical trials for acute lymphoblastic leukaemia during 1980-2002 (N=5601), grouped by address at diagnosis within Great Britain into quintiles of the 1991 Carstairs deprivation index. Children combining severe neutropenia (risk of serious infection) with relatively normal haemoglobin and platelet counts (lack of pallor and bleeding) were postulated to be at risk of dying from infection without leukaemia being suspected. A deficit of these children among diagnosed patients from poorer communities was predicted. RESULTS: As predicted, there was a deficit of children at risk of non-diagnosis (two-sided P(trend)=0.004; N=2009), and an excess of children with pallor (P(trend)=0.045; N=5535) and bleeding (P(trend)=0.036; N=5541), among cases from poorer communities. CONCLUSION: Under-diagnosis in poorer communities may have contributed to socioeconomic variation in recorded childhood acute lymphoblastic leukaemia incidence within Great Britain, and elsewhere. Implications for clinical practice and epidemiological studies should be considered.